Screening by Total Colonoscopy Following Fecal Immunochemical Tests and Determinants of Colorectal Neoplasia in Japanese Men With Alcohol Dependence. (5th October 2016) - Mizukami, Takeshi; Yokoyama, Akira; Yokoyama, Tetsuji; Onuki, Shuka; Maruyama, Katsuya
Abstract: Aims: Alcohol consumption increases the risk of colorectal adenoma and cancer. The fecal immunochemical test (FIT) is a widely used screening method for detecting colorectal neoplasia. We evaluated the results of screening and risk factors for colorectal neoplasia in individuals with alcohol dependence. Methods: Total colonoscopic screening was performed for 1006 Japanese men with alcohol dependence (462 FIT-positive and 544 FIT-negative). Advanced neoplasia was defined as neoplasia ≥10 mm, villous or tubulovillous adenoma, high-grade adenoma, or carcinoma. Results: The detection rates for non-advanced adenoma, advanced neoplasia and intramucosal or invasive carcinoma were 38.7%, 39.4% and 9.7% for the FIT-positive group, and 33.3%, 10.8% and 2.2% for the FIT-negative group, respectively. Advanced neoplasia, especially carcinoma, was detected more frequently in the distal colon than in the proximal colon in the FIT-positive group. The respective multivariate odds ratios (ORs; 95% confidence interval) for non-advanced adenoma and advanced neoplasia were 2.83 (2.06–3.88) and 9.13 (6.19–13.5) for a positive FIT (vs. negative), 1.68 (1.39–2.02) and 1.83 (1.45–2.30) for age (per +10 years), 1.54 (1.06–2.23) and 1.88 (1.17–3.03) for current smoking (vs. non-smokers), and 1.35 (0.96–1.92) and 1.59 (1.02–2.48) for the presence of marked macrocytosis (mean corpuscular volume ≥106 fl vs. <106 fl). Genetic polymorphisms of alcohol dehydrogenase-1B and aldehyde dehydrogenase-2 did not affect the risk of colorectal neoplasia. Conclusion: The detection rate for advanced colorectal neoplasia was extremely high in the FIT-positive group but remained high even in the FIT-negative group. An older age, smoking and macrocytosis were predictors of advanced colorectal neoplasia. Short summary: Total colonoscopic screening was performed for 1006 Japanese alcoholic men (462 fecal immunochemical test [FIT]-positive and 544 FIT-negative). The detection rate for advanced colorectal neoplasia was extremely high in the FIT-positive group (39.4%) and high in the FIT-negative group (10.8%). Ageing, smoking and macrocytosis were predictors of advanced colorectal neoplasia.